Endocrine aspects of menstrual disorders and their correction in overweight women of reproductive age - S S Apetov; S Y Kalinchenko (IP Berlin A.V., 2013)
Insulin resistance in patients with obesity leads to indirect menstrual cycle disruption through hyperinsulinemia and hyperleptinemy. In order to correct menstrual disorders, the metabolic characteristics of the optimal progestin should be considered, so that the already existing disorders of fat and carbohydrate metabolism may not be aggravated even more.